2021
DOI: 10.3390/ma14185405
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Alkali-Activated Blended Binder Mixtures

Abstract: Alkali-activated cement (AAC) is an alternative cement that has been increasingly studied over the past decades mainly because of its environmental benefits. However, most studies are on heat-cured AACs and are focused on mechanical properties. There is a lack of research on the fresh properties of ambient-cured AAC systems. This study investigates the rheological properties of ambient-temperature-cured alkali-activated blended binder mixtures activated with sodium silicate and sodium hydroxide solutions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…This is due to the formation of primary calcium silicate hydrate (C-S-H) gel in the early stages of the reaction due to the bonding of the Ca 2+ ions from the slag to the silicate ions in the sodium silicate. 25 25 reported a similar result. Like compressive strength, the TW/TB ratio, with 59% contribution, is the most significant factor for workability.…”
Section: Setting Timesupporting
confidence: 52%
See 2 more Smart Citations
“…This is due to the formation of primary calcium silicate hydrate (C-S-H) gel in the early stages of the reaction due to the bonding of the Ca 2+ ions from the slag to the silicate ions in the sodium silicate. 25 25 reported a similar result. Like compressive strength, the TW/TB ratio, with 59% contribution, is the most significant factor for workability.…”
Section: Setting Timesupporting
confidence: 52%
“…All the investigated parameters increased workability. Tekle et al 25 reported a similar result. Like compressive strength, the TW/TB ratio, with 59% contribution, is the most significant factor for workability.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This adjustment is crucial to maintain the desired strength of the concrete while simultaneously achieving the desired level of workability [74][75][76]. A higher volume of binder in concrete mixtures decreases particle interactions and friction, leading to an increase in plastic viscosity, ultimately resulting in increasing flowability [77][78][79]. The results also indicate that the increase in L/d has a less significant effect on the slump, regardless of the variations in W/B and SFC values.…”
Section: Rsm Optimizationmentioning
confidence: 92%